PEMODELAN POTENSI EROSI DAN SEDIMENTASI HULU DANAU LIMBOTO DENGAN WATEM/SEDEM - Ardian Alfianto; Shandy Cecilia (Pusat Litbang Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2020)
Erosion and sedimentation caused 4,000-hectare siltation in Limboto. Experts predicted that Limboto will be extinct in 2031. Revitalization program ‘Limboto Lake Revitalization’ has been carried out since 2017, with sabo technology as the action carried out to restrain sedimentation rate and to save the lake from extinction. This study aims to measure erosion and sedimentation potential in upstream of Limboto including 12 rivers (sub-DAS), using WaTEM/SEDEM model Two outputs resulted through this study are total sedimentation potential and identification of sedimentation zoning on each river. Based on soil type and other triggering factors, 5 of 20 rivers have the biggest sedimentation potential to deliver to Limboto, namely Batulayar 193.662 m3, Biyonga Baluta 123.095 m3, Alo1 120.273 m3, Alo 115.204 m3 and Molamahu 73.058 m3. The model was visually calibrated by considering the rivers’ sedimentation volume collected by JICA and BWS Sulawesi II. The result shows different score depending on the soil type, slope, land cover and other parameters. Sabo dam has to be reviewed regularly and on-schedule, since its current data is not actual and upstream rivers have highly dynamic and fluctuative sediment as well.